2021
DOI: 10.1177/07334648211001190
|View full text |Cite
|
Sign up to set email alerts
|

Role of Community Health Workers in Addressing Dementia: A Scoping Review and Global Perspective

Abstract: The current increase in global dementia prevalence deserves public health intervention. While limited access to health care and a shortage of health care workers are significant shortcomings, utilizing community health workers (CHWs) could be a promising way to improve dementia care through cost-effective approaches. This scoping review synthesizes existing research on roles of CHWs in dementia-related services. PubMed, CINAHL, Scopus, CABI Global Health, Web of Science, PsycINFO, and Cochrane Library were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…During MyAlliance development, our community organization partners specifically identified staff training in ADRD as a priority. Numerous studies have demonstrated the efficacy of CHW programs for health education 46,47 . Therefore, we asked partner organizations to help define a curriculum called “Assess.…”
Section: Resultsmentioning
confidence: 99%
“…During MyAlliance development, our community organization partners specifically identified staff training in ADRD as a priority. Numerous studies have demonstrated the efficacy of CHW programs for health education 46,47 . Therefore, we asked partner organizations to help define a curriculum called “Assess.…”
Section: Resultsmentioning
confidence: 99%
“…A successful dementia support program would help bridge this gap by not only educating dyads about dementia and breaking down cultural beliefs around the illness, but also helping to educate providers about these cultural beliefs. Utilizing community health workers as part of the dementia support program team may help facilitate this [ 27 , 28 , 29 ]. Future studies should explore whether the effects of addressing cultural beliefs around dementia early through a dementia support program improve access to care or caregiver burden.…”
Section: Discussionmentioning
confidence: 99%
“…A next step for Oklahoma CHWs and their employers would be to integrate learned dementia knowledge and skills into the CHWs' current workflow. A recent scoping review (Alam et al, 2021) showed that CHWs have the potential to address dementia in several areas. Four studies conducted in the United States showed that CHWs successfully engaged in some services and interventions based on C3 roles, including education and community awareness, dementia screening, utilization of health care systems and other dementia-related resources by patients, and service to dementia caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Our dementia training is a valuable resource in the light of a growing body of evidence reporting the benefits of CHW services in dementia care (Alam et al, 2021). Thus, providing insurance coverage to CHWs trained in addressing dementia will allow greater access to their services.…”
Section: Discussionmentioning
confidence: 99%